Blast control by silicon foliar spray and impairment of photosynthesis by a specific inhibitor increase wheat susceptibility to infection by Pyricularia oryzae - Oliveira, Tássia Boeno (2018)
Considering the effect of blast, caused by Pyricularia oryzae, in reducing wheat yield this study aimed to elucidate if the potassium silicate (PS) polymerization after its foliar spray could compromise the leaf gas exchange (net CO 2 assimilation rate (A), internal CO2 concentration (Ci), stomatal conductance to water vapor (gs) and transpiration rate (E)) and chlorophyll a (maximal photosystem II quantum yield (Fv/Fm), quantum yield of non- regulated energy dissipation [Y(NO)], photochemical yield [Y(II)], electron transport rate (ETR) and quenching non-photochemical [Y(NPQ)]) parameters and, if not, it could become one strategy to reduce blast symptoms on leaf blades. Indeed, if the compromise of the photosynthetic process of wheat plants by using an inhibitor of photosynthesis could increase their susceptibility to blast. There were no significant changes in the values of A, gs, E, Ci, Fv/Fm, Y(NO), Y(II), Y(NPQ) and ETR for plants sprayed three times (96 h interval) with PS rates of 2.5, 5.0, 7.5, 10.0 and 12.5 g L-1. There was no significantly relationship between the PS rates with either absorbance, reflectance or transmittance on the leaf blades. Linear regression model best described the foliar Si concentration-PS rates relationship. Foliar Si concentration was significantly increased by 44 and 42%, respectively, for the PS and PS + fungicide treatments compared to water-sprayed plants. The area under disease progress curve was significantly lower by 64, 57 and 52%, respectively, for the treatments fungicide, PS and fungicide + PS in comparison to water- sprayed plants. No gain on disease control was achieved when PS was mixed with fungicide. The photosynthetical process, especially related to the Fv/Fm parameter, on wheat leaves was greatly impaired during the infection process of P. oryzae, but to a lesser extent on the leaves of PS-sprayed plants. In conclusion, the foliar spray of PS can be an environmental friendly strategy to control wheat blast without inducing any negative impact on the photosynthetic machinery. Plants from cultivar BRS 220, partially resistant to blast, were non-sprayed (control treatment) or sprayed with a solution of 10 μM of 3- (3,4-dichlorophenyl)-1,1-dimethylurea) (DCMU) at 24 h before inoculation with P. oryzae. The DCMU affected the functionality of the photosynthetic apparatus of wheat leaves based on the lower values of net CO2 assimilation rate (A) coupled with increases in the internal carbon concentration. Indeed, there were dramatic reductions in the values of gs and E for infected plants, especially for the DCMU-sprayed ones. The lower A values obtained from leaves of DCMU-sprayed and infected plants limited the carbohydrates synthesis resulting in great starch concentration. Sucrose concentration was reduced on infected leaves mainly if they were sprayed with DCMU while fructose and glucose concentrations increased. The activities of superoxide dismutase and peroxidase were lower while catalase activity was higher for DCMU-sprayed and non-infected plants. Altogether, the results of the present study showed that the spray of DCMU increased wheat susceptibility to blast due to photosynthetic dysfunctions, impairment on sugar metabolism and a less efficient antioxidative system.